Developing A Strategy Map Based on Sustainability Balanced Scorecard Framework for Manufacturing Industry in Indonesia - Nurcahyo, Rahmat; Pustiwari, Saripuji; Sihono Gabriel, Djoko (International Journal of Engineering and Technology, 2018)
This study proposes a structural evaluation to link key performance indicator into a strategy map based on sustainability balanced scorecard framework for manufacturing industry in Indonesia. With four perspectives (finance, stakeholder, internal business process and learning and growth) on Sustainability Balanced Scorecard, the evaluation of relationship between perspectives and indicators of manufacturing industry are synthesized from relevant literature and experts. The Decision Making Trial and Evaluation Laboratory (DEMATEL) method employed to identify critical central and influential factors, to determine the causal relationship and finally to develop a visual strategy map to improve corporate sustainability. The three most important indicators are sustainability award, certification of environmental and social standards and resource productivity. The result can help prioritizing the performance indicators and show which areas that need improvement most.Â Â